Difference between revisions of "009A Sample Final 2, Problem 4"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">Use implicit differentiation to find an equation of the tangent line to the curve at the given point. ::<span class="exam"><math style="vertical-align: -4p...")
 
 
Line 21: Line 21:
 
|Using the product and chain rule, we get
 
|Using the product and chain rule, we get
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; <math>6x+xy'+y+2yy'=5.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>6x+xy'+y+2yy'=0.</math>
 
|-
 
|-
 
|We rearrange the terms and solve for &nbsp;<math style="vertical-align: -5px">y'.</math>
 
|We rearrange the terms and solve for &nbsp;<math style="vertical-align: -5px">y'.</math>
Line 27: Line 27:
 
|Therefore,
 
|Therefore,
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; <math>xy'+2yy'=5-6x-y</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>xy'+2yy'=-6x-y</math>
 
|-
 
|-
 
|and  
 
|and  
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp; <math>y'=\frac{5-6x-y}{x+2y}.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>y'=\frac{-6x-y}{x+2y}.</math>
 
|}
 
|}
  
Line 40: Line 40:
 
|-
 
|-
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
\displaystyle{m} & = & \displaystyle{\frac{5-6(1)-(-2)}{1-4}}\\
+
\displaystyle{m} & = & \displaystyle{\frac{-6(1)-(-2)}{1-4}}\\
 
&&\\
 
&&\\
& = & \displaystyle{-\frac{1}{3}.}
+
& = & \displaystyle{\frac{4}{3}.}
 
\end{array}</math>
 
\end{array}</math>
 
|-
 
|-
 
|Hence, the equation of the tangent line to the curve at the point &nbsp;<math style="vertical-align: -5px">(1,-2)</math>&nbsp; is
 
|Hence, the equation of the tangent line to the curve at the point &nbsp;<math style="vertical-align: -5px">(1,-2)</math>&nbsp; is
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp;<math>y=-\frac{1}{3}(x-1)-2.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>y=\frac{4}{3}(x-1)-2.</math>
 
|-
 
|-
 
|
 
|
Line 56: Line 56:
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp; &nbsp; &nbsp; &nbsp;<math>y=-\frac{1}{3}(x-1)-2.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>y=\frac{4}{3}(x-1)-2.</math>
 
|}
 
|}
 
[[009A_Sample_Final_2|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Final_2|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:37, 14 September 2017

Use implicit differentiation to find an equation of the tangent line to the curve at the given point.

  at the point  
Foundations:  
The equation of the tangent line to    at the point    is
          where  


Solution:

Step 1:  
We use implicit differentiation to find the derivative of the given curve.
Using the product and chain rule, we get
       
We rearrange the terms and solve for  
Therefore,
       
and
       
Step 2:  
Therefore, the slope of the tangent line at the point    is
       
Hence, the equation of the tangent line to the curve at the point    is
       


Final Answer:  
       

Return to Sample Exam